Changes in salinity, aggregates and physicomechanical quality induced by biochar application to coastal soil. Issue 13 (10th November 2023) - Zong, Yutong; Liu, Yaojun; Li, Yanqing; Ma, Ronghui; Malik, Zaffar; Xiao, Qing; Li, Zichuan; Zhang, Jin; Shan, Shengdao
ABSTRACT: Coastal clayey soil has a great potential for food production and safety while poor physico-mechanical properties have impeded its sustainable utilization. A field experiment was conducted to assess the influence of biochar on physicomechanical properties of coastal clayey soil. The biochars were applied to the coastal soil with the rate of 0, 1%, and 3% (w/w), respectively. Compared with control treatment, the application of three biochars (at the rate of 3%) had significantly improved soil fertility, i.e. organic carbon, total nitrogen, available nitrogen and available phosphate, respectively. Biochar treatments significantly increased soil porosity, and aggregates stability, while reduced the soil salinity compared to the control treatment. Meanwhile, biochar application significantly increased the plastic index of coastal clayey soil while decreased soil tensile strength and shrink swell properties compared to the control. Biochar clearly altered soil pore characteristics, consequently rebuilding the new ions leaching channels. Overall, the cow manure biochar (650 °C) at the rate of 3% treatment showed maximum efficiency on soil salinity, fertility, physicomechanical properties, and crop yield. The biochar amendment improved coastal soil by ameliorating soil pore space and structure, improving soil tillage operation and rice yield, decreasing salt stress, and reducing mechanical strength.